Dehumanization and mental health: clinical implications and future directions. (April 2023) - Jenkins, Tom A; Robison, Morgan; Joiner, Thomas E
Abstract : Research shows that people with mental health conditions experience dehumanization, and this is associated with states of emotional distress. Possible sources of meta-dehumanization include interpersonal interactions with members of society, professionals, and institutions, as well as negative portrayals in the news and media. Self-dehumanization may arise from the internalization of these meta-perceptions, interpersonal interactions, or the inherent nature of certain mental health conditions. This article reviews literature on meta- and self-dehumanization within clinical psychology, suggests directions for future research, and provides clinical implications for the field. We advocate for the consideration of self-dehumanization in existing therapies, the development of protocols designed for rehumanization, and the provision of more humanizing care by professionals and society. Highlights: People with mental health conditions experience both self- and meta-dehumanization. Self-dehumanization can be a factor in mental health conditions (e.g. psychosis). Self-dehumanization may act as a conduit between suicidal ideation and action. Therapeutic interventions may be improved via consideration of self-dehumanization.